SOSIALISASI TAMAN BACAAN MASYARAKAT DI KOTA PEKANBARU - Hartika, Yuriza; Yuliani, Febri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
Education is an important factor to alleviate society from ignorance, backwardness and poverty. One of some efforts in developing insights and knowledge on various field of knowledge is by reading and Badan Perpustakaan dan Arsip Pekanbaru has attempted to support this activity by embodying Taman Bacaan Masyarakat (TBM). But the TBM programme is not entirely successful to realize as what it is expected because the capability and skill in socializing and funding are inadequate to provide an appropriate facilities like books and reading room. The purpose of this research is to get to know, to describe, and to analyze the socialization of Taman Bacaan Masyarakat who is done by Badan Perpusatakaan dan Arsip Kota Pekanbaru by forming a technical team or officers service on the field. The theory concept used communication theory consisting of communicators, the content of the message delivered, media used, targets or communicant, the effects arising after socialization. This research used qualitative research methods with an assessment of descriptive data. In data collection, the researcher used interview techniques, observation, documentation and literature study with using Snowball Sampling. After research, it is found that the socialization who is done by the technical team is considered still not optimal. Because after socialized, many people have not knew about Taman Bacaan Masyarakat yet. The information is not up to the communicators and communicant so it affects the success of socialization Taman Bacaan Masyarakat in Pekanbaru.Keywords : Socialization, Taman Bacaan Masyarakat